ON THE MORPHOBIOLOGICAL CHARACTERISTICS OF SOME ENDEMIC PLANTS DISTRIBUTED IN THE FERGANA VALLEY - Ergashali Yu. Rozmatov,; Tursinboy K. Otaboev,; Khusanboy E. Yuldashev, (EPRA International Journal of Research and Development (IJRD), 2022)
The article presents information on revealing the morpho-biological characteristics of some endemic plants scattered in the Fergana Valley, signs of adaptation to environmental conditions, and preservation.